AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI DESA RAPA LAOK KECAMATAN OMBEN KABUPATEN SAMPANG - Syahadatina, Rika (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
This study aims to find out the Planning, Implementation, and Accountability of Village Fund Allocation. Accountability is the obligation to convey accountability or to answer and explain the performance and actions of a person / legal body / collective leadership of an organization to a party entitled or authorized to request information or accountability. Village Fund Allocation is a government-provided financial budget to the village, Derived from the Tax Sharing as well as the Central and Regional Budgets Funds received by the district. Accounting governance has three main objectives, namely accountability, managerial, and supervision. Accountability by the government is a manifestation of the provision of information about any actions or activities and financial management carried out by the government during a period. The implementation of good governance is the main prerequisite for realizing the aspirations of the people in achieving the goals of the nation and state. The research method in this thesis used qualitative descriptive data analysis technique with the transformation of research data in tabulation form. The result of this research shows that the planning and implementation accountability system has applied the principle of transparency and accountability. While the accountability of Village Fund Allocation both technically and administratively is good, but must still get or given guidance from sub-districtgovernment